Determinants of Action Link to Purchasing Decisions for Laku Pandai Services in East Aceh Regency - Maulana, Zefri; 'Ula, Tajul; Sakya, Nailul (Jurnal Manajemen dan Keuangan, 2024)
Action Link at the ami cell 2 store had received an award as the agenty with the most transactions gacor5000, but after receiving the award, the number of transactions obtained in August experienced a decrease in transactions, even though since the opening of Action Link, transactions have always been crowded. Lack of consumer trust in Action Link leads to a low level of purchase decisions, lack of trust because the withdrawal system uses an account book not using a machine, especially at this time fraud is rampant. This is the cause of consumer distrust, then the service from the store and the service provided by Action Link has not been optimal and the service is not optimal resulting in a low level of purchase decisions gacor5000. The purpose of this study is to test the influence of word of mouth, trust, and service quality on purchase decisions. The researcher uses quantitative methods in his research. The location studied was the Action Link agent at the Ami Cell 2¬ store located in Keude Blang Village, Idi Rayeuk District, East Aceh Regency. With a population of 97 respondents, the results of the research that have been conducted show that word of mouth (WOM) has an influence and is significant on the decision to purchase smart practice services in East Aceh. Based on the results of the study, trust has an influence on the decision to purchase smart practice services in East Aceh and the quality of service has an influence on the purchase decision.